2023
DOI: 10.1186/s12931-023-02399-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pulmonary immune function by inhaled cannabis products and consequences for lung disease

Abstract: The lungs, in addition to participating in gas exchange, represent the first line of defense against inhaled pathogens and respiratory toxicants. Cells lining the airways and alveoli include epithelial cells and alveolar macrophages, the latter being resident innate immune cells important in surfactant recycling, protection against bacterial invasion and modulation of lung immune homeostasis. Environmental exposure to toxicants found in cigarette smoke, air pollution and cannabis can alter the number and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 185 publications
(243 reference statements)
0
2
0
Order By: Relevance
“…The hypersensitivity reactions that occur in DLE are responsible for pro-inflammatory mechanisms that lead to tissue infiltration and damage. Studies have shown that cannabinoids are able to inhibit these processes (45)(46)(47). This may explain the improvement seen in the patient in question.…”
Section: Discussionmentioning
confidence: 99%
“…The hypersensitivity reactions that occur in DLE are responsible for pro-inflammatory mechanisms that lead to tissue infiltration and damage. Studies have shown that cannabinoids are able to inhibit these processes (45)(46)(47). This may explain the improvement seen in the patient in question.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the consequences of inhaled cannabis products on lung cells is crucial for discerning their therapeutic potential and potential risks. It necessitates comprehensive research to elucidate the intricate mechanisms underlying the modulation of pulmonary immune responses, providing insights that can inform the development of targeted interventions and therapeutic strategies for lung diseases associated with cannabis use [11]. Testing on Human Hepatocytes is also important to identify or observe any complications to liver cells from consumption of cannabinoids.…”
Section: Introductionmentioning
confidence: 99%